Outcome of ABO-Incompatible Living Donor Kidney Transplantation: A Single Center Observational Study from Nepal - Hamal, Saurav S; Nepali, Rabin; Poudyal, Sujeet; Shah, Dibya S (Journal of Institute of Medicine Nepal, 2023)
Introduction: Kidney transplantation is the most effective treatment for end-stage renal disease (ESRD) patients. However, the increasing number of ESRD patients and the limited availability of living and cadaveric donors has led to a growing waiting list for kidney transplantation. ABO-incompatible transplantation has emerged as an alternative for these patients in Nepal. Methods: This was an observational study of all the patients who underwent kidney transplantation from March 2017-Feb 2019. Data on demography of recipients and donor, blood group, human leukocyte antigen mismatch, induction agent, post-operative complications and creatinine clearance at discharge and one-year post-transplant were collected and analysed. Then we compared patient and kidney graft survival at one year between ABO incompatible and ABO compatible recipients. Results: During the study period, there were total of 124 kidney transplant recipients among them 12 were ABO incompatible and 112 were ABO compatible recipients. The study showed slightly lower patient and graft survival in ABO-incompatible recipients than ABO compatible recipients (83.3% vs 99.2%, p<0.001). However, death-censored graft survival were similar in both groups (100%,p<0.001). The graft function at one year measured by creatinine clearance was better in ABO-incompatible recipients than ABO-compatible recipients (67.1±11.75 vs 61.87±12.82, p<0.001). Postoperative complications were slightly higher, however, complications at one year were lower in ABO-incompatible recipients. Conclusion: The study showed that living donor ABO-incompatible kidney transplant recipients have a good outcome at one year but is associated with greater risks of patient and graft loss at early transplant period compared to ABO-compatible recipients.